2012
DOI: 10.1111/j.1600-0897.2012.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Coagulation, Inflammation, and Angiogenesis are Independently Associated with Preeclampsia

Abstract: Problem Although preeclampsia has been associated with inflammation, coagulation, and angiogenesis, their correlation and relative contribution are unknown. Method of Study About 114 women with preeclampsia, 31 with early onset (EOP) and 83 with late onset preeclampsia (LOP), and 100 normal pregnant controls were included. A broad panel of 32 biomarkers reflecting coagulation, inflammation, and angiogenesis was analyzed. Results Preeclampsia was associated with decreased antithrombin, IL‐4 and placental growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 36 publications
5
70
1
1
Order By: Relevance
“…Some of the inconsistencies regarding Treg cells may refer to how they were defined (Mjosberg et al 2009). Although there is disagreement on the role of Treg cells in preeclampsia, there is agreement that preeclampsia is associated with a shift of the Th1/Th2 balance toward Th1 immune responses in severe preeclampsia (Boij et al 2012;Borzychowski et al 2005;Darmochwal-Kolarz et al 1999, 2002Makhseed et al 1999). In mild preeclampsia, however, it was shown that the maternal immune response is shifted toward a Type 2 immune response (Veenstra van Nieuwenhoven et al 2008).…”
Section: Pregnancy-induced Changes In the Systemic Adaptive Immune Rementioning
confidence: 99%
“…Some of the inconsistencies regarding Treg cells may refer to how they were defined (Mjosberg et al 2009). Although there is disagreement on the role of Treg cells in preeclampsia, there is agreement that preeclampsia is associated with a shift of the Th1/Th2 balance toward Th1 immune responses in severe preeclampsia (Boij et al 2012;Borzychowski et al 2005;Darmochwal-Kolarz et al 1999, 2002Makhseed et al 1999). In mild preeclampsia, however, it was shown that the maternal immune response is shifted toward a Type 2 immune response (Veenstra van Nieuwenhoven et al 2008).…”
Section: Pregnancy-induced Changes In the Systemic Adaptive Immune Rementioning
confidence: 99%
“…In a previous study, the plasma levels of CXCL10 were increased in patients with preeclampsia, and the plasma levels of CXCL11 were elevated significantly in early-onset preeclampsia patients compared with control patients (P<0.05) (58).…”
Section: Chemokines and Preeclampsiamentioning
confidence: 99%
“…29 immune responses has been associated with spontaneous abortions [119,120], pre-eclampsia [121] and pre-term labour [122]. Similarly, Th17-like immunity has been associated with spontaneous abortions [123,124] and might be detrimental for the pregnancy in combination with a Th1 deviated immunity.…”
Section: Review Of the Literaturementioning
confidence: 99%